2008
DOI: 10.3390/s8053123
|View full text |Cite
|
Sign up to set email alerts
|

Plant Species Recovery on a Compacted Skid Road

Abstract: This study was executed to determine the plant species of herbaceous cover in a skid road subjected to soil compaction due to timber skidding in a beech (Fagus orientalis Lipsky.) stand. Our previous studies have shown that ground based timber skidding destroys the soils extremely, and degradations on ecosystem because of the timber skidding limit recovery and growth of plant cover on skid roads. However, some plant species show healthy habitat, recovery and they can survive after the extreme degradation in st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 49 publications
2
3
0
2
Order By: Relevance
“…Primary revegetation on coalmining spoils in Agacli-Istanbul, the best-represented species belongs to Rosaceae. Similarly, some similar plant species determined in this study show the resistance and survival capability on degraded soils in some research areas close to the Agacli mine spoils (Demir et al, 2008).…”
Section: Resultssupporting
confidence: 73%
“…Primary revegetation on coalmining spoils in Agacli-Istanbul, the best-represented species belongs to Rosaceae. Similarly, some similar plant species determined in this study show the resistance and survival capability on degraded soils in some research areas close to the Agacli mine spoils (Demir et al, 2008).…”
Section: Resultssupporting
confidence: 73%
“…Any disturbance to the forest ecosystem and/or soil affects adversely the native ground flora (Zenner et al 2006;Demir et al 2008), but some plant species are capable to show healthy habitat and a rapid recovery after extreme degradation of the soil (Demir et al 2008). Zenner and Berger (2008) reported that the soil compaction resulted in shifting of ground flora from interior forest species to noxious/invasive and disturbed forest species and relative resistance of the initial ground flora to change was found to be linearly related to relative resistance to penetration.…”
Section: Ground Floramentioning
confidence: 99%
“…The first two types usually have a gravel surface protection, while the latter are simply a loose soil. Skid trails are defined as tertiary roads that are used by skidders that move logs from the point of felling and bucking to log landings (Demir et al 2008).…”
mentioning
confidence: 99%